Induction of apoptosis in A549 pulmonary cells by two Paracoccidioides brasiliensis samples - Del Vecchio, Adriana [UNESP]; Silva, Julhiany de Fatima da [UNESP]; Silva, Juliana Leal Monteiro da [UNESP]; Andreotti, Patricia Ferrari [UNESP]; Soares, Christiane Pienna [UNESP]; Benard, Gil; Mendes-Giannini, Maria José Soares [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 2009)
Paracoccidioidomycosis presents a variety of clinical manifestations and Paracoccidioides brasiliensis can reach many tissues, most importantly the lungs. The ability of the pathogen to interact with host surface structures is essential to its virulence. The interaction between P. brasiliensis and epithelial cells has been studied, with particular emphasis on the induction of apoptosis. To investigate the expression of different apoptosis-inducing pathways in human A549 cells, we infected these cells with P. brasiliensis Pb18SP (subcultured) and 18R (recently isolated from cell culture and showing a high adhesion pattern) samples in vitro. The expressions of Bcl-2, Bak and caspase 3 were analysed by flow cytometry and DNA fragmentation using the TUNEL technique. Apoptosis of human A549 cells was induced by P. brasiliensis in a sample and time-dependent manner. Using an in vitro model, our data demonstrates that caspase 3, Bak, Bcl-2 and DNA fragmentation mediate P. brasiliensis-induced apoptosis in A549 cells. The overall mechanism is a complex process, which may involve several signal transduction pathways. These findings could partially explain the efficient behaviour of this fungus in promoting tissue infection and/or blood dissemination.
Keywords: apoptosis; Paracoccidioides brasiliensis; caspase 3; Bak; Bcl-2